Bridging the gap between horizontal and vertical merger simulation: Modifications and extensions of PCAID - C. Anthony Bush (Kiel Institute for the World Economy (IfW), 2014)
A general theoretical and empirical framework is developed for assessing the potential of a vertically integrated firm to foreclose downstream competitors. Using this framework a policymaker may also evaluate the empirical welfare effects from a vertically integrated firm raising rivals' costs. The framework is developed within the context of a vertically integrated multichannel video programming distributor ("MVPD"), and this framework extends the applicability of PCAIDS to vertical mergers. Using public data from the Comcast-Time Warner-Adelphia Merger Order of the Federal Communications Commission, price effects from the threat and action of foreclosure in several designated marketing areas were simulated. Empirical results suggest that the Commission Staff Model substantially underestimated price increases to end users as a result of the threat and action of foreclosure. Empirical results suggest that Commission's Program Access Rules were essential for MVPD competition.
Keywords: C15; C01; C02; C53; C61; D4; K2; L1; L96; 330; Mergers; merger simulation; vertical merger; horizontal merger; telecommunications; PCAIDS; foreclosure; raising rival's cost; two-sided markets